The implementation of software process improvement models. - Ismail, Mohammad Hafiz; Jusoff, Kamaruzaman (2009)
This research attempts to identify and analyze the extent of Capability Maturity Model Integration (CMMI) and other associated process model or frameworks in Malaysian organizations. There is a number of studies have been conducted on software process improvement by using above models and methodologies in other continents such as Europe, Australia, New Zealand and North America. However, there is still lack of published studies on software process improvement or software best practices in Southeast Asia, especially Malaysia itself. Surveys in Malaysian software organizations which have an experience in initiating and conducting software process improvement initiative have been done. The surveys were conducted by using paper survey and also online survey. Two different type of survey was conducted because of the different risk or constraint of cost, time, and distance can be overcome. There were 20 respondents involved in this research. Most of the respondents were professionals who are directly involved in SPI initiative. In the data analysis, the respondents are characterized according to the attribution of weight to their answers. We found that the IT Malaysian organizations are employing CMMI, Prince 2, PMBOK and also Six Sigma. This study shows that Malaysian organizations have already take an initiative to adopt software process improvement models in their organization